1994
DOI: 10.1108/02656719410057935
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Effects of Quality Improvement Activities on Business Performance

Abstract: Quality improvement activities Delegated Voluntary Taguchi Total quality teams teams SPC ISO 9000 techniques management Employee communication Departmental communication Supplier communication Customer communication Vendor performance Business control Quality costs Employee morale Product quality Table IV. Questionnaire Question

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 1 publication
3
94
0
Order By: Relevance
“…Most of the previous studies report that overall TQM practices have positively been related to productivity and manufacturing performance [4,5], quality performance [6][7][8][9], employee satisfaction/performance [3,7], innovation performance [3,9,10], customer satisfaction/results [5,7,11,12], competitive advantage [13,14], market share [15], financial performance [7,13,[16][17][18], and aggregate firm performance [1,3,11,14,[19][20][21][22][23]. However, some authors have found negative or insignificant results [15,24,25].…”
Section: Overall Tqm Practicesmentioning
confidence: 99%
“…Most of the previous studies report that overall TQM practices have positively been related to productivity and manufacturing performance [4,5], quality performance [6][7][8][9], employee satisfaction/performance [3,7], innovation performance [3,9,10], customer satisfaction/results [5,7,11,12], competitive advantage [13,14], market share [15], financial performance [7,13,[16][17][18], and aggregate firm performance [1,3,11,14,[19][20][21][22][23]. However, some authors have found negative or insignificant results [15,24,25].…”
Section: Overall Tqm Practicesmentioning
confidence: 99%
“…This employee involvement tends to increase their quality perspectives (Juran and Gryna 1993). If an organization wants to flourish itself and equip with TQM then it has to work on employee education and training (Mann et al 1993). The above discussion puts more emphasis on Leadership as compared to vision and plan statement, employee participation and education and training.…”
Section: Introductionmentioning
confidence: 99%
“…Sidin and Wafa (2014) who researched on Malaysian manufacturing industries including rubber also confirmed the positive relationship between QM and organisational performance. Further, most of the previous studies report that QM practices have positively been related to OP with respect to different manufacturing organisations (Chenhall, 1997;Mann & Kehoe, 1994). Moreover, as explained by the Resource Based View of the firm (Escrig-Tena, 2003) unique resources and competencies can be generated by implementing quality management practices.…”
Section: Operational Performancementioning
confidence: 99%